Samuel Palmer and Romanticism - Chapman, Anton (Rhodes University, Faculty of Humanities, Department of Fine Art, 1985)
This introduction and ensuing essay are something in the nature of a personal confession. Deemed as such what I have written concerning Samuel Palmer has not, in any way, been written as an exercise, but rather for the purpose of self-edification. This I will elaborate upon while disclosing my motive for writing on Palmer. Palmer's works - when I first saw them - were something of a revelation. They seemed the alpha and omega of my own artistic endeavour. Perhaps the term which best describes the euphoria I felt is 'deja vu', because although it describes a connectedness of sorts, the words have in their sound an exotic ring. There is in it an implied equivocation - and equivocality best describes my understanding of Samuel Palmer at that juncture. This euphoria I felt dimmed with the realisation that by purportedly claiming, as I was, Samuel Palmer's visionary landscapes as my goal I was treading on sacred ground; I'd arrived, as it were, in another's Paradise. The effects of this upon my own creativity were completely negative. Worse still, I lacked the necessary means to extricate myself from Palmer's paradisiacal visions. His influence was incapacitating and convoluting my own growth. It was obvious then that I had to be rid of Samuel Palmer.
Keywords: Palmer, Samuel, 1805-1881 -- Criticism and interpretation; Romanticism in art; Blake, William, 1757-1827 -- Influence; Landscape painting, English -- 19th century